PERENCANAAN KOMUNIKASI PEMERINTAH DAERAH KABUPATEN SIAK DALAM IMPLEMENTASI KEBIJAKAN PEMBANGUNAN KABUPATEN LAYAK ANAK (KLA) - Nova Yohana (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
The development program of Child-Friendly City (KLA) in Siak Regency is a development system based on children rights through a comprehensive and sustainable integration of government, society and business world thoroughly and continuously. Implemented based on instruction from Ministry of Women and Child Empowerment (P3A), through Ministerial Regulation (Permen) Number 11 Year 2011 on the Development Policy of Child-Friendly City. The purpose of this research is to find the communication planning of local government in the implementation of the program for Child-Friendly City through prioritizing children rights in regional development, Siak regency. The method that being used for this researh is qualitative method. The research informants were chosen puposively and the data were collected through observation, interview, and documentation. The results of the research shows that the process of arrangement in order of Child-Friendly City policy communication planning has gone through the stages of a policy formulation. The purpose of the Child-Friendly City development program is being implemented into the vision and mission of Siak Regency development with the preparation of regional action plans. The audience that being targeted for the implementation of Child-Friendly City development is the whole society in Siak Regency either individually or in groups. Messages are designed in relation to the role of target audience related to the fulfillment of children's rights in Siak Regency development. In an effort to inform Child-Friendly City program policies, media selection takes into consideration the characteristics and objectives of the message content submitted, and the type of media owned by audiences. Program evaluation emphasizes in order for the regional apparatus to evaluate what its authority and duties are in support the Child-Friendly City program and plan according to the needs of Child-Friendly City in Siak Regency.